Neutrophil extracellular traps in ischemic stroke: mechanisms, clinical implications, and therapeutic potential - He, Wenbo; Wu, Zuoli; Liu, Ying; Ye, Ziming (Frontiers in Neurology, 2025)
Ischemic stroke remains a leading cause of mortality and disability, with many patients failing to benefit from reperfusion therapies due to lysis-resistant thrombus formation and severe neuroinflammation. This highlights an urgent need to target the fundamental mechanisms linking these two processes. Neutrophil extracellular traps (NETs)—web-like structures of DNA and cytotoxic proteins—have emerged as a critical mediator of stroke pathology. While essential for host defense, their dysregulated formation in the cerebral microvasculature drives a vicious cycle of tissue injury. This review synthesizes evidence demonstrating that NETs are not mere bystanders but active drivers of stroke pathology. We dissect the core mechanisms by which they mediate three primary detrimental effects: (1) promoting stable, lysis-resistant thrombi, which directly contributes to poor clinical outcomes; (2) compromising blood–brain barrier integrity; and (3) amplifying the neuroinflammatory cascade. Furthermore, we evaluate the clinical utility of NETs as powerful biomarkers for diagnosis and prognosis, and we critically analyze emerging therapeutic strategies aimed at dismantling them. While targeting NETs with agents like DNase I or PAD4 inhibitors holds immense promise, we argue that significant translational challenges—such as ensuring therapeutic specificity and defining the optimal treatment window—must be overcome. In conclusion, targeting the thrombo-inflammatory functions of NETs represents a paradigm shift from a purely fibrin-centric view of stroke, opening new avenues for developing more effective therapies.